Neural networks and neuro-fuzzy systems applied to the analysis of selected problems of geodesy - Mrówczyńska, Maria (Computer Assisted Methods in Engineering and Science, 2017)
The article presents possibilities of using different artificial neural networks and neuro-fuzzy systems to solve certain engineering geodesy tasks. Special attention is paid to tasks connected with the construction of a numerical terrain model, transformation of coordinates from the "1965" system into the "2000" system, and prediction of a time series on the basis of results of GPS measurements. The paper also includes a short description of those neural networks and neuro-fuzzy systems that provided good quality solutions of the tasks undertaken. The goal of the article is to review the papers published in the years 2005-2010.